A Parametric Investigation of Geometric Variation on Fluid Dynamic Instabilities in Axial Compression Systems. (4th December 2012) - Sivaramakrishnan Malathi, Ananth; Kushari, A.
Abstract : The ability to predict the nature of instabilities is highly important from the compressor design point of view since their consequences could result in widely varying difficulties with the fluid dynamic performance of the systems. Even though the behavior of surge and rotating stall is reported in many literatures, it is noticed that an in-depth analysis is not undertaken. Hence in view of the importance for a deeper understanding, the present paper is aimed at tracking the chaos of these instabilities in a more detailed manner. Primarily the influence of geometric parameters on the nature of surge and rotating stall is investigated. The effect of each of the major geometric parameters such as compressor effective length, annulus area, and plenum volume is discussed. The physical reason for the onset of instabilities is also explained in each case, and the well-accepted Moore-Greitzer model has been used for the present study. The combined effect of physical parameters is determined through the Greitzer B parameter. The results shown in this paper clearly elucidate the dominating effect of the geometric parameters on the development of flow instabilities like rotating stall and surge and hence can serve as a design guideline to avoid such instabilities.